THE EFFECT OF STOCK LIQUIDITY, PROFIT MANAGEMENT, INFORMATION ASYMETRY AND PROFITABILITY ON THE COST OF EQUITY CAPITAL AT CONVENTIONAL COMMERCIAL BANKS LISTED ON THE INDONESIA STOCK EXCHANGE IN 2018-2022 - Damaria Silalahi; Agave Orasi Manik; Mika Anggreini Pandiangan; Marselia Siburian; Januardin Januardin; Rintan Br. Saragih (SEAN Institute, 2023)
The purpose of this study is to determine and evaluate the effect partially and simultaneously of the variables of stock liquidity, earnings management, information asymmetry, and profitability on the cost of equity capital in conventional commercial banks listed on the Indonesia Stock Exchange (IDX) on the Indonesia Stock Exchange. from 2018 to 2022. Multiple linear regression is the data analysis strategy applied in this study. There are 43 companies listed on the Indonesia Stock Exchange, based on the corporate population between 2018 and 2022. There are 10 companies sampled with a total of 50 companies sampled at conventional commercial banks. The results of the study show that partially stock liquidity and profitability have a negative and insignificant effect on the cost of equity capital in conventional commercial banks listed on the IDX in 2018-2022. Meanwhile, partially, information asymmetry and earnings management have a positive and significant effect on the cost of equity capital in conventional commercial banks listed on the IDX in 2018-2022. The results show that simultaneously stock liquidity, information asymmetry, earnings management and profitability have a significant positive effect on the cost of equity capital in conventional commercial banks listed on the IDX in 2018-2022. The results of the coefficient of determination show that stock liquidity, information asymmetry, earnings management and profitability contribute 46.29% to the cost of equity capital,